GUPPI Educational Institutions (1968-1992) - Nasution, Ahmad Taufik; Ansori, M Afif; Andari, An An; Pribadi, Joko; Kholil, Muhamad (Yupa: Historical Studies Journal, 2024)
This research aims to examine the efforts of GUPPI in reforming Islamic education in Indonesia. This study employs a literature review methodology, utilizing a qualitative approach with a historical method. Data is collected through literature from various journals and relevant websites concerning the research subject. The findings reveal that GUPPI experienced fluctuations, both during the New Order era and the Reform era. During the New Order era, GUPPI saw institutional development in assets and territory, indicating significant progress due to its political ties with Golkar. However, GUPPI's idealism to further develop Islamic education stagnated during the Reform era. In the VII GUPPI Congress in 1998, GUPPI disaffiliated from the Golkar party and returned to being an independent organization. Post-VII and VIII Congresses from 2005 to 2011, GUPPI continued to grapple with internal issues and sought strategies for revival.